Understanding Court Culture and Improving Court Performance in 12 Courts in California, Florida, and Minnesota, 2002 - Ostrom, Brian J. ([Verlag nicht ermittelbar], 2008)
The purpose of this study was to examine the organizational culture in 12 felony criminal trial courts selected in 3 states and to gauge prosecuting and public defender attorneys' views on how well the courts in which they practice achieve the goals of access, fairness, and managerial effectiveness. Data on organizational culture in each of the 12 courts (Part 1) were obtained by administering the Court Culture Assessment Instrument (CCAI) to all judges with a felony criminal court docket and to all senior court administrators. A total of 224 respondents completed the questionnaire. Additionally, surveys were conducted of prosecuting attorneys (Part 2) and public defender attorneys (Part 3) to gauge their views on how well the courts in which they practice achieve the goals of access, fairness, and managerial effectiveness. A total of 334 prosecuting attorneys and 260 public defense attorneys completed the 46-item trial court process survey. Part 1 contains 40 variables pertaining to 5 dimensions of current and preferred court culture. Variables in Part 2 and Part 3 each include seven items from a jurisdictional practice scale, eight items from a procedural fairness scale, seven items from a resource scale, nine items from a management scale, nine items from a practitioner competence scale, and six items from a court access scale.